Suffering doubly: Effect of cyberbullying on interpersonal deviance and dual mediating effects of emotional exhaustion and anger - Syed, Nausheen; Hamid, Abu Bakar Abdul; Su, Xin; Bhatti, Misbah Hayat (Frontiers in Psychology, 2022)
Research on employee harassment, in the form of workplace bullying, has increased over the past decade. However, there is little research on the prevalence and impact of cyberbullying, a type of cyber-related violence in the workplace. Thus, it would be interesting to examine the impact of cyberbullying on interpersonal deviance through the serial mediating effect of emotional exhaustion and anger. Drawing from the conservation of the resource theory and the affective event theory, this proposed study clarifies the mediating effects of emotional exhaustion and anger. The time lag approach was used to collect the data from the sample of 385 employees in the telecommunication sector of Pakistan. By employing SPSS and PLS, bootstrapping was performed to conduct the mediation analysis. Findings indicated that workplace cyberbullying increased interpersonal deviance by enhancing emotional exhaustion and anger. The current research contributes to the literature by considering the behavioral outcomes of workplace cyberbullying with the practical implications for human resource practitioners.